Effect of Beam-Steering Angle, Operation Wavelength and Mean Inter-Element Distance on the Side-Lobe Levels of Integrated Optical Phased Arrays under Beam-Steering Operation - Aldaya, Ivan [UNESP]; Pires de Souza, Bruna Dias [UNESP]; Penchel, Rafael Abrantes [UNESP]; Pita, Julian Leonel; dos Santos, Mirian Paula [UNESP]; de Oliveira, José Augusto [UNESP]; Abbade, Marcelo Luis Francisco [UNESP] (MDPI, 2023)
Integrated optical phased arrays (OPAs) play an important role in a broad range of applications. Fabrication constraints, however, pose a limit to the minimum inter-element separation that further results in high-intensity side lobes. The intensity of these secondary lobes can be reduced by arranging the antenna elements with non-uniform separation distance, which has been addressed by different methods. In this paper we employ one of the already proven optimization algorithms, i.e., differential evolution, to optimize the element positions of linear arrays with different configurations operating under beam-steering operation and considering a minimum inter-element distance. These optimizations allowed us to derive some design guidelines that can assist in reducing the side-lobe level (SLL) of integrated linear OPAs. In particular, we found that it is necessary to optimize the positions for the broadest beam-steering angle and the shortest operation wavelength. Additionally, optimizations of different configurations reveal that, when imposing a minimum inter-element distance, there is an optimum mean distance that minimizes the SLL of the array.
Keywords: differential evolution; optical phased arrays; side-lobe level